2016
DOI: 10.1038/mi.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Fc receptor-mediated phagocytosis in tissues as a potent mechanism for preventive and therapeutic HIV vaccine strategies

Abstract: While the development of a protective HIV vaccine is the ultimate goal of HIV research, to date only one HIV vaccine trial, the RV144, has successfully induced a protective response. The 31% protection from infection achieved in the RV144 trial was linked to the induction of non-neutralizing antibodies, able to mediate ADCC, suggestive of an important role of Fc-mediated functions in protection. Likewise, Fc-mediated antiviral activity was recently shown to play a critical role in actively suppressing the vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 59 publications
(83 reference statements)
5
84
0
Order By: Relevance
“…It has been suggested that nonneutralizing mechanisms, such as phagocytosis, neutrophil activation, and ADCC, are likely to play a role in both HIV prevention and reservoir-eliminating therapeutic approaches (77,78). This is supported by the RV144 clinical trial where a correlate of reduced infection was found with various Fc-mediated activities but not with neutralization (9-18).…”
Section: Discussionmentioning
confidence: 50%
“…It has been suggested that nonneutralizing mechanisms, such as phagocytosis, neutrophil activation, and ADCC, are likely to play a role in both HIV prevention and reservoir-eliminating therapeutic approaches (77,78). This is supported by the RV144 clinical trial where a correlate of reduced infection was found with various Fc-mediated activities but not with neutralization (9-18).…”
Section: Discussionmentioning
confidence: 50%
“…ADCP may contribute more to vaccine-elicited protection than ADCC, particularly in mucosal tissues (33). ADCP was enhanced in recipients of the RV144 vaccine with a high level of IgG3/IgG1 Abs to V1-V2 (34) and was associated with protection in nonhuman primates (29).…”
mentioning
confidence: 99%
“…This suggests that the in vivo antitumor activity of this fusion protein can be retained by its apoptotic effects and CDC in mice with diminished NK cell activity. Macrophages and neutrophils are also known to exhibit ADCC function (13). It is possible that macrophages and neutrophils can replace the ADCC function of NK cells for this fusion protein in SCID-beige mice.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that although 2B8T2M induces antitumor activity through ADCC, the in vivo antitumor activity of this fusion protein is retained by its apoptotic effects and CDC against tumor cells in mice with diminished NK cell activity. Macrophages and neutrophils are also known to exhibit ADCC and antibody-dependent cellular phagocytosis functions (13). It is possible that macrophages and neutrophils contribute to the antitumor activity of this fusion protein in the SCID-beige mice.…”
Section: Journal Of Biological Chemistry 23875mentioning
confidence: 99%